Tourism Destination Evaluation in Uzbekistan: Assessing Key Regions through the Lens of Competitiveness and Lifecycle Stages - Ibrokhimov Nodirbek (Academia Open, 2025)
General Background: Tourism has become a strategic sector for Uzbekistan’s economic diversification, driven by its rich cultural heritage and increasing international visibility. Specific Background: Major destinations such as Tashkent, Samarkand, Bukhara, and Khiva exhibit differing performance levels that require systematic evaluation using established tourism frameworks. Knowledge Gap: Existing studies largely rely on descriptive approaches and rarely integrate quantitative destination competitiveness indicators with tourism lifecycle analysis at the regional level. Aims: This study quantitatively assesses the competitiveness and lifecycle stages of key Uzbek destinations by integrating the Tourism Area Life Cycle (TALC) model with the Travel and Tourism Competitiveness Index (TTCI). Results: Findings indicate that Tashkent and Samarkand demonstrate higher arrivals, ADR, RevPAR, and occupancy rates, positioning them in the consolidation stage, whereas Bukhara and Khiva show lower economic performance and characteristics of maturity, with challenges in attracting high-spending international tourists. Novelty: The study provides one of the first empirical, region-specific analyses in Uzbekistan that simultaneously applies competitiveness and lifecycle frameworks using quantitative indicators. Implications: The results inform evidence-based destination management, highlighting the need for sustainability strategies in advanced destinations and targeted infrastructure, marketing, and product diversification to rejuvenate mature cities and strengthen Uzbekistan’s long-term tourism competitiveness.Highlight : Tashkent and Samarkand show the strongest competitiveness and are in the consolidation stage of the tourism life cycle. Bukhara and Khiva perform at lower levels, indicating maturity-stage destinations needing regeneration. Sustainability and cultural preservation are essential for long-term tourism competitiveness. Keywords :Uzbekistan Tourism, Destination Competitiveness, Tourism Area Life Cycle, Travel and Tourism Competitiveness Index, Sustainable Tourism